Dinâmica do glifosato em latossolo vermelho distroférrico fertirrigado com água residuária da suinocultura - Mallmann, Larissa Schmatz (2009)
The increase in agriculture on foodstuff demand asked for an alternative of development and expansion, as well as the use of chemicals that could increase productivity. The use of glyphosate herbicide is an example, since it is mainly applied on soybean crop. The western Paraná State turns up as an important producer of grains and swine, but the wastes produced on swine activity are also potential environmental polluters when wrongly managed. So, the use of swine wastewater comes as an alternative source of microorganisms to degrade this herbicide in soil. In this study, it was evaluated the glyphosate displacement in soil, using swine wastewater as a source of microorganisms and organic matter. Four acrylic columns were prepared with soil (sterile or not), wastewater or distilled water and a glyphosate solution (112.5 g L-1). After the preparation, the columns were incubated for seven days in BOD incubator at 23°C, so that microorganisms could be adapted to the medium. Then, the leaching test was carried out and the samples were analyzed by high-performance liquid chromatography. The treatments showed similar behavior among themselves and there was no peak that could represent glyphosate. This suggests that it has been adsorbed or was mineralized. At last, organic matter did not influence any treatment.